Concepts of psychological well-being in three waves of cognitive-behavioral therapy - ABRAMOV, Volodymyr (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
This article analyzes the concepts of psychological well-being and the mechanisms of its achievement in three waves of cognitive-behavioral therapy (CBT): the behavioral therapy of the first wave, the classical cognitive therapy of A. Ellis and A. Beck of the second wave, and the contextual therapies of the third wave. The ideal of psychological well-being in classical behavioral therapy involves an individual’s frustration tolerance, enabling a change in their response to uncomfortable stimuli. Primary methods to achieve this ideal include step-by-step desensitization and the development of alternative behaviors through operant conditioning. Classical cognitive therapy by A. Ellis and A. Beck operates with a more comprehensive model, considering personal factors influencing reactions to stimuli. This has led to the development of correction techniques for erroneous thinking strategies, viewed as distortions in objective information processing. Consequently, the ideal of psychological well-being is seen as a more realistic perception of reality, achieved through correcting cognitive constructs such as automatic thoughts and core beliefs aligning them with reality through testing, such as behavioral experiments. According to proponents of the second wave, individuals should adopt a scientist’s mindset by formulating and testing hypotheses. In the third wave of CBT, the ideal of psychological well-being involves individuals adopting a detached observer position toward events in their inner world, including thoughts, emotions, and core beliefs. Additionally, great importance is placed on individuals pursuing their own values. The mechanism for achieving this ideal involves changing the context of distress-inducing thoughts without altering their content. Despite some contradictions between the views of the second and third waves of CBT, the techniques of these approaches are consistent and can be used sequentially. Corrections in thought processes, as facilitated by second-wave therapy, can change the status of thoughts from being perceived as objective truths, which can be further deepened through third-wave techniques, altering the status of thoughts from objects to contextual elements in an individual’s life.